A H-shaped heterometallic Sn4Au4 system with guest-tuneable multicolour and selective luminescence sensing properties. Issue 39 (20th June 2018) - Jobbágy, Csaba; Baranyai, Péter; Gömöry, Ágnes; Deák, Andrea
Abstract : A H-shaped heterometallic Sn4 Au4 system displays guest-dependent optical properties and its stimuli-responsive methylred-rich crystals are sensitive towards pH variations. Abstract : A H-shaped heterometallic Sn4 Au4 system that displays tuneable guest-dependent optical and photoluminescent properties has been synthesized. It shows selective dye sorption, while its stimuli-responsive methylred-rich solid is sensitive towards pH variations. This non-emissive Sn4 Au4 system exhibits multicolour luminescence in the presence of aniline derivatives.